The Effect of Pulley Reconstruction on Maximum Flexion, Bowstringing, and Gliding Coefficient in the Setting of Zone II Repair of FDS and FDP: A Cadaveric Investigation. (March 2014) - Stanbury, Spencer J.; English, Christopher; Yaseen, Zaneb; Reed, Jeffrey D.; Chen, Tony; Awad, Hani; Elfar, John C.
Purpose: The purpose of this experiment was to determine the effect of A2 pulley reconstruction on gliding coefficient (GC), bowstringing, and proximal interphalangeal (PIP) joint maximum flexion angle after zone II repair of flexor digitorum superficialis (FDS) and flexor digitorum profundus (FDP) lacerations. Methods: Fresh frozen cadaver forearms were mounted, and the wrist and MCP joints fixed. FDS and FDP tendons were dissected free, and sequential loads were applied while digital images were captured. The dissected digit with intact native A2 pulley, FDS, and FDP tendons was used as the control (group 1). Zone II lacerations followed by four-stranded repair of FDP plus epitendinous suture and repair of FDS were then performed, and the data recorded (group 2). A2 pulley excision and reconstruction with a loop of palmaris longus autograft was then completed and the specimens sequentially loaded and photographed (group 3). Using the digital images, GC, bowstringing, and maximum flexion angle were calculated. Results: No difference in maximum flexion angle was observed across the three testing conditions. Zone II laceration and subsequent FDS and FDP tendon repair significantly increased the GC for group 2 specimens; however, pulley reconstruction alleviated some of this increase for group 3. Bowstringing was significantly greater after pulley reconstruction, with a mean increase of 1.9 mm at maximum flexion for group 3 specimens relative to group 1 controls. Discussion: Strong flexor tendon repairs are needed to prevent gap formation and subsequent triggering; however, the increased bulk from these large repairs can itself produce deleterious triggering, as well as tendon abrasion. Pulley reconstruction, in the setting FDP and FDS repair (group 3), significantly reduced the GC relative to tendon repair alone (group 2). While bowstringing was significantly greater after pulley reconstruction (group 3), it averaged only 1.9 mm over group 1 specimens and did not compromise maximum flexion angle compared to the uninjured controls (group 1) or the isolated tendon repair digits (group 2).